Availability of breastfeeding peer support in the United Kingdom: A cross‐sectional study. Issue 1 (7th July 2017) - Grant, Aimee; McEwan, Kirsten; Tedstone, Sally; Greene, Giles; Copeland, Lauren; Hunter, Billie; Sanders, Julia; Phillips, Rhiannon; Brown, Amy; Robling, Mike; Paranjothy, Shantini
Abstract: Peer support is recommended by the World Health Organization for the initiation and continuation of breastfeeding, and this recommendation is included in United Kingdom (U.K.) guidance. There is a lack of information about how, when, and where breastfeeding peer support was provided in the U.K. We aimed to generate an overview of how peer support is delivered in the U.K. and to gain an understanding of challenges for implementation. We surveyed all U.K. infant feeding coordinators ( n = 696) who were part of U.K.‐based National Infant Feeding Networks, covering 177 National Health Service (NHS) organisations. We received 136 responses (individual response rate 19.5%), covering 102 U.K. NHS organisations (organisational response rate 58%). We also searched NHS organisation websites to obtain data on the presence of breastfeeding peer support. Breastfeeding peer support was available in 56% of areas. However, coverage within areas was variable. The provision of training and ongoing supervision, and peer‐supporter roles, varied significantly between services. Around one third of respondents felt that breastfeeding peer‐support services were not well integrated with NHS health services. Financial issues were commonly reported to have a negative impact on service provision. One quarter of respondents stated that breastfeeding peer support was not accessed by mothers from poorer social backgrounds. Overall, there was marked variation in the provision of peer‐support services for breastfeeding in the U.K. A more robust evidence base is urgently needed to inform guidance on the structure and provision of breastfeeding peer‐support services.